Ocular manifestations in tuberculosis cases with HIV in Nepal - Bhatta, Subash; Shah, D. N.; Choudhary, Meenu; Thakur, Ajit; Pant, Nayana (Nepalese Journal of Ophthalmology, 2019)
Introduction: TB has seen resurgence associated with HIV. Tuberculosis can affect any ocular tissue. The association of HIV with TB is supposed to increase the incidence and plethora of ocular manifestations in tuberculosis. Objectives: To study the various ocular manifestations seen in tuberculosis patients with associated HIV infection. Material and Methods: This hospital based, cross sectional descriptive study was conducted in Tribhuvan University, Teaching Hospital, Maharajgunj, Nepal and Geta Eye Hospital, Kailali from 2010 to 2015. Diagnosed cases of pulmonary and extra pulmonary tuberculosis with HIV co infection were evaluated for ocular manifestations after excluding other opportunistic infections. Results: Of 70 cases eligible for the study, extra pulmonary tuberculosis was seen in60% of the cases. 5 patients (7.1 %) had ocular manifestations. CD4 counts were <50/mm3 in 3 cases. Ocular involvement was seen in the form of choroidal granulomas, papillitis, cranial nerve palsy, retinal vasculitis and central serous chorioretinopathy. Conclusion: This study demonstrated that ocular involvement is a frequent finding in cases with tuberculosis and HIV. Ocular findings are more common in cases with lesser CD4 counts. As ocular tuberculosis can be visually devastating, we recommend regular ocular evaluation of all patients with HIV and systemic tuberculosis.